La formazione giovanile di Leonardo tra Vinci e Firenze - Alessandro Vezzosi (Firenze University Press, 2020)
Decades of research have led to the discovery of decisive documents and new interpretations that have allowed to update Leonardo's youthful biography, the history of his family - in particular the role of the merchant and traveller grandfather - and the context of his training: in Vinci (emblematic name for its "knots"), in Bacchereto and in Florence (prior to when it was not previously believed). The youthful experiences are revealed in the early start to art and they develop thanks to the stories of distant countries, in the dream of flight, in the projects of deviation of the Arno and in the vision of the landscape in aerial perspective...